2014
DOI: 10.1016/j.crci.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of pyrimidines under solvent-free conditions

Abstract: N,N,N',N'-Tetrabromobenzene-1,3-disulfonamide was used as an efficient catalyst for the one-pot synthesis of pyrimidine derivatives in excellent yields from triethoxymethane, ammonium acetate, and various ketone derivatives at 100-110 8C under solvent-free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…At this stage, we speculate that the intermediate (III) reacts with the orthoester to form intermediate (IV) . Finally, it was observed that cyclization and aromatization of intermediate (IV) results in the final product (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, we speculate that the intermediate (III) reacts with the orthoester to form intermediate (IV) . Finally, it was observed that cyclization and aromatization of intermediate (IV) results in the final product (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
“…Also, three‐component coupling reaction catalyzed by ZnCl 2, TBBDA, TsOH and Boron sulfuric acid provides the synthesis of various 4,5‐disubstituted pyrimidine derivatives via one‐pot reaction from acetophenones, triethylorthoformate, and ammonium acetate. In view of the green chemistry, we tried in this work to substitute harmful substrate by magnetic nano‐Fe 3 O 4 based on pyridine as a novel nanocatalyst which contains surface high density Br 3 − in the synthesis of pyrimidines, so, we propose a new route for the synthesis of pyrimidines, from one‐pot reaction of triethoxymethane, various ketones and ammonium acetate using nano‐magnetic functional pyridiniunm‐tribromide (TBP‐SCMNPs), as a novel catalyst and choline chloride/urea mixture as a deep eutectic solvent (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 Optimization of reaction conditions for the synthesis of trisubstituted 1,2,4-triazines a 15 Entry Solvent The probable mechanism of these catalysts is based on releasing 5 Br + in situ, which can act as an electrophilic species. [23][24][25][26][27] Therefore, the mechanism shown in Scheme 2 may be suggested for the conversion of the various doctrines, acid hydrazides and ammonium acetate to trisubstituted triazines. 28 95 5,6-Bis(4-methoxyphenyl)-3-(p-tolyl)-1,2,4-triazine ( 10 3-Phenyl-5,6-di(p-tolyl)-1,2,4-triazine ( 25 5,6-Diphenyl-3-(pyridin-4-yl)-1,2,4-triazine ( 3-(Pyridin-4-yl)-5,6-di(p-tolyl)-1,2,4-triazine ( …”
Section: Resultsmentioning
confidence: 99%
“…Recently, Wu and coworkers reported a novel diastereoselective one-pot three-component reaction 50 containing urea/thiourea, various aldehydes and alkenes for the synthesis of pyrimidinone (thione) derivatives using TMS-Cl. [20][21][22][23][24][25][26] They react under heterogeneous conditions, are conveniently handled and after completion of the reaction, the sulfonamide was recovered, rebrominated and used for several times (Scheme 2). 18 55 Although several methods are available for the preparation of furano and pyrano pyrimidinones (thiones), some of them suffer from disadvantages such as long reaction time, low yields of products, the use of toxic metal reagents and strongly acidic conditions.…”
Section: Introductionmentioning
confidence: 99%